Patient-sharing networks among Finnish primary healthcare professionals taking care of patients with mental health or substance use problems: a register study - Christian Hakulinen; Marko Elovainio; Jaana Suvisaari; Timo Sinervo; Laura Hietapakka; Visa Väisänen; Ripsa Niemi; Mai Gutvilig; Outi Linnaranta (BMJ Open)
Objectives Patient-sharing networks based on administrative data are used to understand the organisation of healthcare. We examined the patient-sharing networks between different professionals taking care of patients with mental health or substance use problems.Design Register study based on the Register of Primary Health Care visits (Avohilmo) that covers all outpatient primary health care visits in Finland.Setting We used the register data covering the visits for the service providers of seven municipalities, adult patients with at least one visit to a health and social service centre within one of the municipalities and visits during the year 2021.Participants We first selected patients with mental health or substance use problems based on psychiatric diagnoses and information on service type and then identified the professionals (N=1566) visited. A patient-sharing relationship was defined between two professionals if a same patient had visited both of them at least once.Primary outcome measures We analysed the potential associations of the network structure and the nodal attributes (municipality, belonging to a certain occupational group and the service type) with nodal formation using Exponential Random Graph Models.Results The main findings showed that two professionals were more likely to share patient(s) when they belonged to the same occupational group, provided similar types of services or worked in the same municipality. Being a physician was associated with having more connections to other professionals than belonging to other occupational groups (OR for nurses 0.70, 95% CI 0.69 to 0.7 and for other occupations 0.83, 95% CI 0.81 to 0.84). Shared patients among different professionals were also more probable when the patients were shared with the professionals working within mental health or substance use services compared with outpatient healthcare services (OR 1.64, 95% CI 1.61 to 1.67).Conclusions Patient-sharing contacts were mainly homogenous, supporting the tendency of people to have connections with similar people. The results also highlight the role of the physicians as important partners in the patient-sharing networks.